METHOD FOR MEASUREMENT OF COORDINATES OF POWER CENTRE OF EXTENDED LASER PATH IMAGES (Transport systems and technologies, 2018)
In the article authors have worked out a nonstationary signal analysis method on an example of research of laser paths. This method disclosed relationship between sig-nal approximation coefficients and geometry signal characterizations (for example, energy center, moment of inertia). An example, which is demonstrating an application of this method for exact coordinate determination problem in laser paths at displace-ment compensation in laser imaging are present.
Keywords: parallel-hierarchical network, laser path, real-time image sequences, dy-namic tunnelling system.